Emergency TREPP for Strangulated Inguinal Hernia Repair: A Consecutive Case Series - Zwols, T.L.R.; Akkersdijk, W.L.; Bökkerink, W.J.V.; Andeweg, C.S.; Pierie, J.P.E.N.; Koning, G.G. (The Surgery Journal, 2020)
Background Patients with strangulated inguinal hernia (SIH) require emergency surgical treatment. International guidelines do not specify the surgical technique of preference. Frequently, an open anterior approach such as the Lichtenstein technique is used.The TransREctus sheath Pre-Peritoneal (TREPP) technique is an alternative, open posterior approach, which has shown promising results in the elective treatment of inguinal hernias. This study aims to evaluate the feasibility and safety of the TREPP technique in the emergency setting of SIHs.Materials and Methods After medical ethical approval was warranted, all consecutive patients, who underwent emergency TREPP (e-TREPP) at a high-volume hernia institute, were retrospectively included from 2006 up to and including 2016. Data retrieved from the electronic patient files were combined with the findings during a long-term outcome physical investigation at an outpatient department visit. e-TREPP was, prior to the start of the study, defined as TREPP performed immediately at the operation room.Results Thirty-three patients underwent e-TREPP for SIH. Ten patients were clinically evaluated, ten patients were deceased, nine patients could not be contacted, and four patients did not or could not consent. Of the ten deceased patients, one patient died perioperatively due to massive aspiration followed by cardiac arrest. Nine patients died due to other causes. Two patients developed a recurrence after (after 13 days and 16 months respectively). Two patients were surgically treated for a wound infection (mesh removal in one). No patient reported chronic postoperative inguinal pain.Conclusion e-TREPP in experienced hands seems feasible and safe (Level of Evidence 4) for the treatment of patients with strangulated inguinal hernia, with percentages of postoperative complications comparable to other techniques.
Keywords: strangulated inguinal hernia; incarcerated; TREPP; open preperitoneal; extraperitoneal; emergency